PENGARUH PROMOSI DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN SARIAYU PUTIH LANGSAT - Herawati, Heny; Muslikah, Muslikah (Kinerja, 2019)
This study is purposed to obtain empirical evidence about the problem under study, namely the Effect of Promotion and Packaging Design on Purchasing Decisions of Sariayu Putih Langsat Products at PT. Martina Berto Tbk. This research was conducted on 91 consumers of Sariayu white langsat products that have been selected as samples, sampling with random sampling, data analysis with multiple linear regression using SPSS 20. Based on data analysis and discussion, partially the promotion variable has a positive but not significant effect on purchasing decisions where t count 1.565 <t table 1.987 and the significance level of 0.121> 0.05. The packaging design variable partially has a positive but not significant effect on purchasing decisions where t count 1.374 <ttable 1.987 and the significance level of 0.173> 0.05. Simultaneously obtained F count of 5.137> F table 3.10 with a significance level of 0.008 <0.05, it can be concluded that Ha is accepted, meaning that promotion and packaging design has a positive and significant effect on purchasing decisions. The coefficient of determination (R2) of 10.5% means that the promotion and packaging design variables have little influence on purchasing decisions. The conclusions of this study are (1) Promotion has a positive effect but not significantly on purchasing decisions, (2) Packaging design has a positive but not significant effect on purchasing decisions, (3) Promotion and packaging design simultaneously has a positive and significant effect on purchasing decisions, (4) Variable promotion and small packaging design influence on purchasing decisions.